Characterization and mechanical properties of PLA/acetylated cellulose nanocrystals composites for dental crown prototype application - Ikhsanul Fikri Fakhrurrozi; Muhammad Kusumawan Herliansyah; Kusmono (Results in Engineering)
In this work, a single screw extruder was used to fabricate composite filaments based on polylactic acid (PLA) containing various acetylated cellulose nanocrystals (ACNC) contents (0, 0.5, 1, and 1.5 wt%). These filaments were then used to fabricate the 3D-printed samples using fused filament fabrication (FFF). Characterizations were conducted on the filaments and 3D-printed samples using Fourier-transformed infrared (FT-IR), x-ray diffractometer (XRD), thermogravimetric analysis (TGA), and surface roughness. The mechanical properties were also determined using tensile, compressive, and flexural tests. The TGA analysis revealed that adding ACNC significantly enhanced the thermal performance of the neat PLA. Moreover, the presence of ACNC on 3D printed samples improved the water absorption but decreased the solubility. The presence of ACNC enhanced the surface roughness but reduced the wear resistance with ACNC content up to 1 wt%. In addition, the presence of 0.5 wt% ACNC in the filament increased the tensile strength and decreased with the further addition of ACNC. For 0° orientation on 3D-printed samples, the tensile and compressive strength was improved with the ACNC addition of 1 wt% into the neat PLA by 11 and 40 %, respectively. However, for the orientation of 90°, the presence of ACNC decreased the compressive strength. The flexural strength decreased with the addition of ACNC by up to 1 wt% and then increased with the addition of 1.5 wt%. Overall, acetylated-reinforced PLA composites had great potential for applying dental crown prototypes.